2006
DOI: 10.1007/bf02850159
|View full text |Cite
|
Sign up to set email alerts
|

A 3-month clinical trial comparing the IOP-lowering efficacy of bimatoprost and latanoprost in patients with normal-tension glaucoma

Abstract: This multicenter, randomized, double-blind clinical trial was undertaken to compare the intraocular pressure (IOP)-lowering efficacy and safety of topical bimatoprost 0.03% with that of latanoprost 0.005% for the treatment of patients with normal-tension glaucoma. After washout of all ocular hypotensive medications, patients with normal-tension glaucoma (n=60) were randomly assigned to oncedaily bimatoprost 0.03% or latanoprost 0.005% for 3 mo. Diurnal IOP measurements were taken at each study visit. Primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
2
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 11 publications
6
22
2
2
Order By: Relevance
“…18 Achievement of an IOP reduction greater than 30% as recommended by the CNTG study group is very difficult using a single, topical antiglaucoma eye drop. [10][11][12][13]17,18,20,21 In our study, the rates of 30% IOP reduction are 23.5% for maximum 24-hour IOP and 11.8% for mean 24-hour IOP. When a topical combination therapy is needed to achieve the target reduction in IOP, travoprost without BAK is a superior option because preservatives such as BAK can induce conjunctival inflammation and affect success rates for filtering surgery.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…18 Achievement of an IOP reduction greater than 30% as recommended by the CNTG study group is very difficult using a single, topical antiglaucoma eye drop. [10][11][12][13]17,18,20,21 In our study, the rates of 30% IOP reduction are 23.5% for maximum 24-hour IOP and 11.8% for mean 24-hour IOP. When a topical combination therapy is needed to achieve the target reduction in IOP, travoprost without BAK is a superior option because preservatives such as BAK can induce conjunctival inflammation and affect success rates for filtering surgery.…”
Section: Discussionsupporting
confidence: 46%
“…In previous studies, IOP reduction by latanoprost 0.005% and bimatoprost 0.03% in NTG has been reported to be in the range of 12.7% to 20% and 16% to 21.6%, respectively. 10,13,20,21 Travoprost 0.004% has been reported to have similar results (16.7% to 25.1%). 17,18 Our results are in accordance with the results of these previous studies.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Ten of the 15 trials involved a PGA. 44,53,56,103,114,169,[170][171][172][173] Subjects (n = 1571) switched to latanoprost from previous glaucoma monotherapy and fixed and unfixed combination therapies maintained IOP to an acceptable level through a 2-year period. 174 Latanoprost-insensitive patients developed IOP lowering with bimatoprost in a randomized prospective study with two 30-day treatment phase and 30-day washout phase.…”
Section: Rank Order Of Ocular Hypotensives As Monotherapymentioning
confidence: 99%
“…Bimatoprost was superior in IOP lowering to travoprost only during the daytime (0800 and 1200 hours time-points), but latanoprost and travoprost were comparable at all time points (P # 0.82). 88 An industry-sponsored meta-analysis 90 of travoprost vs latanoprost (15 trials, n = 1098), 57,68,85,93,95,96,[98][99][100] travoprost vs bimatoprost (8 trials, n = 714), 57,85,87,93,95,96,101,102 and latanoprost vs bimatoprost (8 trials, n = 943) 57,64,85,86,93,95,96,103 found similar efficacy among the three PGAs. Studies comparing the PGA to other non-PGA glaucoma treatments, nonrandomized, dose-finding or cross-over trials, and short-term evaluations (less than 3 months) were excluded, although a trial evaluating timolol plus travoprost versus timolol alone, 100 was included indicating that the PGA effect has the same relative effect as if it were compared with no treatment.…”
mentioning
confidence: 99%